Chronic ankle instability: the value of talar tilt under general anaesthesia. Issue 2 (June 1995) - McCaskie, A W; Gale, D W; Finlay, D; Allen, M J
Abstract : Ankle inversion injuries are the most common injury in sport and yet treatment is controversial. One result is chronic ankle instability, an injury for which criteria for surgical intervention are unclear. This prospective study of 14 patients showed that a large proportion of patients had no detectable abnormality on preoperative investigation, but were subsequently shown to have an abnormality under general anaesthesia. This suggests that a good history of chronic instability is more sensitive an indicator than conventional investigations. Stress views under anaesthesia may confirm the problem.